2008
DOI: 10.1590/s0102-09352008000100018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the risk of contracting Lyme disease in areas with significant human presence

Abstract: In order to describe seasonal changes in Lyme disease risk rate at three localities in Serbia, a total of 1,542 Ixodes ricinus ticks (493 nymphs; 525 females, and 524 males) were examined from 2003 to 2004. The prevalence of Borrelia burgdorferi in Ixodes ricinus ticks at the Bovan Lake County was higher than the average for European localities (45.9% for adults and 18.8% for nymphs). In Mt. Avala and Kljajićevo counties, adults and nymphs were infected at the following percentages: 26.3 and 10.7; 16.2 and 7.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the other hand, a different study (Tomanović et al, 2010) found that over 40% of I. ricinus ticks were infected with these bacteria, similar to the results of the current study. According to prior studies (Milutinovic et al, 2008;Radulović et al, 2010;Tomanović et al, 2010), the following Borrelia species are found in Serbian ticks: B. afzelii, B. garinii, B. valaisiana, and, most frequently, B. lusitaniae.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, a different study (Tomanović et al, 2010) found that over 40% of I. ricinus ticks were infected with these bacteria, similar to the results of the current study. According to prior studies (Milutinovic et al, 2008;Radulović et al, 2010;Tomanović et al, 2010), the following Borrelia species are found in Serbian ticks: B. afzelii, B. garinii, B. valaisiana, and, most frequently, B. lusitaniae.…”
Section: Discussionmentioning
confidence: 94%
“…In central, western, and northern Europe, Ixodes ricinus , also known as the castor bean tick, is the most widespread tick species ( de la Fuente et al, 2017 ; Rosa et al, 2018 ). This species has been frequently reported to infest humans and is ( Milutinovic et al, 2008b ) the main vector for a large variety of TBPs transmitted to both humans and animals. Other tick species, such as the ornate cow tick Dermacentor reticulatus , the red sheep tick Haemaphysalis punctata , and the brown dog tick Rhipicephalus sanguineus s.l., are also widely distributed across Europe where reports of tick bites by these species in human is increasing ( Rubel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA extracted from individual ticks was used as a template, as described previously (Radulović et al Seasonal dynamics of I. ricinus populations in Serbia with extremes of interest for the current study marked: 1, the beginning of tick activity; 2, spring peak; 3, summer minimum; 4, autumn peak. Graph is based on previous results (Milutinović and Bobić 1997, Milutinović 2000, Milutinović and Radulović 2002, Milutinović et al 2008 2010). In the Þrst step, reverse transcription and ampliÞcation of 913 bp long sequence was performed by using SuperScript III One-Step RT-PCR System with Platinum Taq High Fidelity (Invitrogen, Carlsbard, CA), as well as ZR-GPDH-913-F and ZR-GPDH-913-R primers.…”
Section: Methodsmentioning
confidence: 99%